2013
DOI: 10.1080/00380768.2013.858300
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth and mineral accumulation of two solanaceous species,Solanum scabrumMill. (huckleberry) andS. melongenaL. (eggplant), under salinity stress

Abstract: Solanum scabrum Mill. (huckleberry) is widespread in West, East and Central Africa, where it constitutes one of the most important leafy vegetables. However, the salinity tolerance of this crop has not yet been assessed. The objective of this study was to assess the response of huckleberry to salinity stress in comparison with eggplant (S. melongena L.). Four-week-old seedlings of both species were subjected to two levels of salinity stress, 50 mM and 150 mM sodium chloride (NaCl), for 14 d. Leaf water potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
(54 reference statements)
1
20
0
5
Order By: Relevance
“…2). This pattern offers further support to the existence of a mechanism of Na + exclusion to the leaf blade in huckleberry (Assaha et al, 2013). The present study further revealed that in addition to stem and root, the petiole also appears to be a potential control point for Na + delivery to the leaf blade.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…2). This pattern offers further support to the existence of a mechanism of Na + exclusion to the leaf blade in huckleberry (Assaha et al, 2013). The present study further revealed that in addition to stem and root, the petiole also appears to be a potential control point for Na + delivery to the leaf blade.…”
Section: Discussionsupporting
confidence: 52%
“…The huckleberry and eggplant used in this study were the same as described in Assaha et al (2013). Seeds of both plants were sown in seed beds, transferred 4 weeks after germination to 2 L pots, filled with a mixture of regosol soil, perlite and peat moss (2: 1: 1, v/v) and irrigated with ¼ nutrient solution for 10 d. Thereafter, the plants were arranged in a randomized complete block design with 4 groups of 4 replicates each and irrigated with ½ strength nutrient solution, supplemented with 0 (for control) and 150 (stressed) mM NaCl to induce salinity stress.…”
Section: Plants and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations